Simulation of vibration signal generated by a defective rolling element bearing. (2016) - Paliwal, D.; Choudhury, A.; Govardhan, T.
With the advent of vibration-based fault detection techniques a lot of work has been done to identify flaws of rolling element bearing through the processing of simulated and experimental vibration signals. This paper is aimed to describe the methodology of developing a simulated signal of a defective rolling element bearing which can replicate the experimental vibration signal emanated under similar condition. Various factors like change in bearing rotational speed, radial load, defect width, pseudo periodicity and bearing parameters have been considered to generate simulated signals. Components of characteristic defect frequencies obtained through simulated signals have been compared with the experimental results of previous researchers wherein a fair resemblance in patterns authenticates the generation of simulated signals through proposed methodology.